2018
DOI: 10.2478/mipo-2018-0008
|View full text |Cite
|
Sign up to set email alerts
|

Mineralogy, chemical composition and leachability of ash from biomass combustion and biomass–coal co-combustion

Abstract: Ash samples from biomass combustion or co-combustion with coal were analysed. The aim of this study of ash was to determine its mineral and chemical composition, and the chemical composition of solutions obtained during one-step water extraction. Besides the chemical analysis, X-ray diffraction (XRD) and scanning electron microscopy coupled with energy dispersive spectrometry (SEM-EDS) were applied. The mineral and chemical composition of ash samples differ strongly. The content of heavy metals in the ash is g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
6
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 44 publications
(59 reference statements)
5
6
4
Order By: Relevance
“…Comparing our results with the findings of Wilczyńska-Michalik et al [12], it can be safely concluded that the macronutrient content is mostly convergent, especially with regard to P 2 O 5 and K 2 O. However, the concentration of CaO as well as S in the CFB fly ash differed more significantly compared to both findings.…”
Section: Macro and Micronutrient Contents In Biomass Fly Ash In Accorsupporting
confidence: 77%
See 3 more Smart Citations
“…Comparing our results with the findings of Wilczyńska-Michalik et al [12], it can be safely concluded that the macronutrient content is mostly convergent, especially with regard to P 2 O 5 and K 2 O. However, the concentration of CaO as well as S in the CFB fly ash differed more significantly compared to both findings.…”
Section: Macro and Micronutrient Contents In Biomass Fly Ash In Accorsupporting
confidence: 77%
“…However, the concentration of CaO as well as S in the CFB fly ash differed more significantly compared to both findings. For the fly ash samples CFB1 and CFB2, the concentration of CaO ranged from 12.86 to 14.07 wt%, which was found to be lower than the CaO concentration reported by Wilczyńska-Michalik et al [12] (18.56 wt% CaO). On the other hand, the fly ash examined during our study was richer in sulfur content (1.58-1.83 wt%) than the fly ash examined by Wilczyńska-Michalik et al [12] (1.12 wt%).…”
Section: Macro and Micronutrient Contents In Biomass Fly Ash In Accorcontrasting
confidence: 68%
See 2 more Smart Citations
“…The content of heavy metals in biomass ash presented in [32] was generally below the limits for fertilizers or soils. However, the significant variability in mineral and chemical composition of ash indicates that a comprehensive examination of ash samples is necessary to determine the possible scope of its application.…”
Section: Appl Sci 2019 9 X For Peer Review 6 Of 16mentioning
confidence: 85%